The Motherhood Penalty and Female Employment in Urban India - Das, Maitreyi Bordia; Zumbyte, Ieva (World Bank, Washington, DC, 2017)
Since the 1990s, India has seen robust economic growth, rising wages, steady fertility decline, increased urbanization, and expanded educational attainment for males and females. But unlike other countries that have undergone similar transitions, urban women's employment has refused to budge, never crossing the 25 percent mark. This paper fills a critical gap in policy research on women's employment in India. The discussion is situated in the normative construction of motherhood and the gendered nature of caregiving in India. The analysis uses pooled data from six rounds of the National Sample Surveys to examine the effects of having a young child on mothers' employment in urban India over 1983-2011. The analysis also looks at household structure, and analyzes the effects of other household members on women's labor supply. The results show that although the onus of childbearing may have reduced, that of caregiving has increased. Having a young child in the home depresses mothers' employment, an inverse relationship that has intensified over time. Further, living in a household with older children and women over the age of 50 is positively associated with women's employment. These results show that the care of young children is an increasingly important issue in women's employment decisions, in a context where formal childcare is practically nonexistent. These results have significant implications for policy to raise women’s labor force participation in India.